Predictive occupational safety management in shipping - Xu, Xuewei (2015)
Seafaring is regarded as a dangerous occupation due to its inherent risks. Historically, seafaring was associated with high mortality and morbidity rates. A great number of researches related to occupational safety management in shipping focused on the technical side of shipping while more than 50% of fatal cases are a result of occupational accidents happening onboard vessels rather than shipping accidents. Therefore, this study focused on the occupational accidents happened onboard vessels in the Singapore context. In total, 10 indicators were selected based on their frequency of mentioning in existing literature, namely age, education, experience, workload, job content, provision of safety equipment, training and drills, safety culture, reward system and accountability. Both quantitative and qualitative analyses were applied in this research study. Industry knowledge was obtained through in-depth interview with experts from shipping companies and ship management companies. First-hand data from survey of seafarers was then collected and used to analyse the applicability of each indicator adopting hypothesis testing and regression analysis. It was found that moderate to significant correlations existed between accountability (β=0.23), experience (β =0.25), safety culture (β =0.65), job content (β =0.19), training and drills (β =0.13) and the effectiveness in occupational hazards management. Reward system (β =0.02), age (β =0.03), workload (β = -0.04) and education (β=0.01) are less effective as indicators. Due to the limited sample size, caution should be taken when applying the research results in company operations. Multiple indicators are recommended to be considered in order to achieve a holistic understanding of the risk picture. Further studies with larger sample size are recommended to reduce the potential error and generalize the results in this research.